Price gouging laws and goods’ prices in post-disaster times - Aguirre Horno, Jon (Filosofia, ara! Revista per a pensar, 2016)
Abstract: In this paper I defend Price gouging laws, ie, laws that control prices in post-disaster situations, and critic Michael Gilberson’s arguments against Price gouging laws from his defense of free market even in post-disaster situations. Keywords: Price gouging laws, free market, Michael Gilberson.